Electropolymerization and multifunctional properties of novel polypyrrole films embedded with Co nanoparticles. (20th February 2017) - Gao, Min; Lu, Liying; Xu, Xiaoguang; Yao, Zhe; Jiang, Yong
Abstract: A novel electropolymerization process has been presented to prepare compact polypyrrole (PPy) polymer films embedded with different cobalt nanoparticle (Co NP) loadings by using cyclic voltammetry. An electropolymerization mechanism is suggested and further confirmed by Fourier transform infrared (FT-IR) spectroscopy and Raman spectroscopy of pure PPy and PPy polymer nanocomposites (PNCs). The PPy/Co PNCs exhibit unique multifunctional properties. Firstly, they are superparamagnets at room temperature, whose saturation magnetization can be controlled by modifying the concentration of Co NPs in the electrolyte solution. Secondly, they show not only semiconductor transportation behavior but also a negative magnetoresistance under external magnetic field. The permittivity of the PPy/Co PNCs switches from negative to positive with the increasing frequency. Both the outstanding magnetic and electrical properties make the PPy PNCs promising as one kind of microwave absorbing materials.